Vanadate catalyst as well as preparation method and application thereof
By preparing a vanadate catalyst with a core-shell structure, the problem of poor catalytic activity of vanadate catalysts at low temperatures is solved, and efficient NOx emission reduction and sulfur resistance under low temperature conditions are achieved, suitable for 180℃-400℃ Catalytic applications within range.
Patent Information
- Application Number
- CN202411697425.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2024-12-24
AI Technical Summary
The poor catalytic activity of existing vanadate catalysts at low temperatures limits their application in the field of NOx emission reduction, especially when the temperature is below 230°C.
The vanadate catalyst with a core-shell structure is zirconium vanadate and the shell structure is ceria. It is prepared by hydrothermal reaction and stirring to ensure uniform dispersion of vanadium and zirconium and pass through the dioxide in the shell structure. Cerium forms a covalent bond with sulfur dioxide, protecting the nuclear structure from sulfur contamination.
The catalytic activity and sulfur resistance of vanadate catalysts at low temperatures have been improved, and the NO conversion rate remains 90%, and the NO conversion rate reaches more than 80% within the range of 180℃-400℃, which is suitable for a variety of low-temperature catalytic scenarios.
Smart Images

Figure CN119175094A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a vanadate catalyst and a preparation method and application thereof. Background Art
[0002] Nitrogen oxides (NO x ) includes compounds such as nitric oxide, nitrogen dioxide, and nitrous oxide. x The main sources of NO are mobile sources and fixed sources. Mobile sources include exhaust emissions from diesel ships and motor vehicles, which release a large amount of NO during combustion. x Stationary sources are mainly waste gases from power plants, industrial furnaces and chemical plants. These facilities produce a large amount of NO when burning fossil fuels and conducting industrial production. x . NO x Excessive emissions of NO pose a serious threat to the environment and human health. x It will directly stimulate the respiratory system, leading to health problems such as difficulty breathing and decreased lung function. x It is one of the main components of photochemical smog and haze, which will aggravate air pollution and endanger public health. x It can also cause acid rain, destroy the ecological balance of soil and water, and corrode buildings and cultural heritage. x In the atmosphere, it will participate in the destruction of the ozone layer, weaken the earth's barrier function against ultraviolet rays, and at the same time, act as a greenhouse gas, promoting global warming.
[0003] In order to cope with the increasingly stringent NOx emission standards, Selective Catalytic Reduction (SCR) has become the most widely used NO x Emission reduction technology. NH3-SCR technology introduces ammonia (NH3) into the exhaust gas at high temperature, and under the action of the catalyst, the ammonia and NO x The reaction generates harmless nitrogen and water. SCR catalyst is the key to the process, and commonly used catalysts include precious metal catalysts, transition metal oxide catalysts and transition metal ion exchange zeolite catalysts.
[0004] Compared with traditional vanadium-based catalysts, vanadate catalysts show significant advantages in catalytic performance, environmental friendliness and sulfur resistance. The high melting point of vanadate catalysts improves their thermal stability and reduces the risk of catalyst deactivation under high temperature conditions. Its environmental friendliness is reflected in the fact that vanadium exists in the form of anions and is not easily absorbed by organisms, thus showing better environmental compatibility. However, the catalytic activity of vanadate catalysts obtained in the existing technology at low temperatures is poor, especially when the catalytic environment temperature is lower than 230°C, which limits the performance of vanadate catalysts in NOx Application in the field of emission reduction. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a vanadate catalyst and a preparation method and application thereof. The vanadate catalyst obtained by the present invention not only has good catalytic activity at low temperatures, but also has good sulfur resistance and nitrogen selectivity.
[0006] The invention provides a vanadate catalyst, which has a core-shell structure, wherein the core structure is zirconium vanadate (ZrVO4) and the shell structure is cerium dioxide (CeO2).
[0007] Furthermore, the vanadium and zirconium of the zirconium vanadate are in an amorphous state and are uniformly dispersed in the core structure.
[0008] The present invention also provides a method for preparing the vanadate catalyst, which comprises: Step S1: adding a solution containing ammonium metavanadate to a solution containing a zirconium precursor, mixing evenly, adding ammonia water to adjust the pH, performing a hydrothermal reaction, performing solid-liquid separation, washing, drying, and calcining to obtain a core structure; Step S2: dissolving and dispersing the core structure, adding a cerium precursor, mixing evenly, dropping ammonia water to adjust the pH, solid-liquid separation, washing, drying, and calcining to obtain a vanadate catalyst with a core-shell structure.
[0009] Furthermore, the zirconium precursor includes one or more of zirconium nitrate, zirconium oxynitrate, and zirconium nitrate pentahydrate.
[0010] Furthermore, in the solution containing ammonium metavanadate, the concentration of the ammonium metavanadate in the solution is 0.24 mol / L in terms of vanadium ions.
[0011] Furthermore, in the solution containing the zirconium precursor, the concentration of the zirconium precursor in the solution is 0.24 mol / L in terms of zirconium ions.
[0012] Furthermore, in the step S1, after uniform mixing, the ammonium metavanadate is calculated as vanadium element, the zirconium precursor is calculated as zirconium element, and the molar concentration ratio of the ammonium metavanadate and the zirconium precursor is 1:1.
[0013] Furthermore, in the method for preparing the solution containing ammonium metavanadate, the ammonium metavanadate is dissolved and dispersed in deionized water.
[0014] Furthermore, in the method for preparing the solution containing the zirconium precursor, the zirconium precursor is dissolved and dispersed in deionized water.
[0015] It should be understood by those skilled in the art that uniform mixing can only be achieved when the ammonium metavanadate and the zirconium precursor are fully dissolved and dispersed. Therefore, when preparing a solution containing ammonium metavanadate and a solution containing a zirconium precursor, a water bath heating method can be adopted to promote the full dissolution of the ammonium metavanadate and the zirconium precursor, and a stirring method can also be adopted during the water bath heating process to further promote the dissolution and dispersion of the raw materials. As an example, stirring can be performed for 30 minutes at a water bath temperature of 80°C.
[0016] Furthermore, the uniformly mixed solution may be stirred before the hydrothermal reaction to enable the solute to be evenly dispersed, and the stirring time is 50 min-70 min.
[0017] Furthermore, in step S1, the concentration of aqueous ammonia is 0.9 mol / L-1.1 mol / L.
[0018] Furthermore, in step S1, ammonia water is added dropwise to adjust the pH to 9.
[0019] In the present invention, stirring is beneficial to the sufficient precipitation of the precipitate from the reaction of ammonium metavanadate and zirconium precursor. Those skilled in the art can adjust the stirring time and stirring speed according to the actual situation, so as to facilitate the complete precipitation of the precipitate.
[0020] Furthermore, in step S1, the temperature of the hydrothermal reaction is 170° C.-190° C., and the time of the hydrothermal reaction is 11 h-13 h.
[0021] Furthermore, in step S1, the specific method of washing includes washing with distilled water and anhydrous ethanol in sequence until the pH of the product is 7, and the washing is completed.
[0022] Furthermore, in step S1, the drying temperature is 70°C-90°C, and the drying time is 11h-13h.
[0023] Furthermore, in the step S1, the calcination temperature is 440°C-460°C, and the calcination time is 3.5h-4.5h.
[0024] Furthermore, in the step S1, the heating rate to reach the calcination temperature is 5.5°C / min-6.5°C / min.
[0025] Furthermore, the cerium precursor includes one or more of cerium nitrate and cerium nitrate hexahydrate.
[0026] Furthermore, in the step S2, after uniform mixing, the molar concentration ratio of the core structure to the cerium precursor is 1-2:1-4, calculated as cerium element in the cerium precursor and zirconium element in the core structure.
[0027] Furthermore, in the step S2, after uniform mixing, the molar concentration ratio of the core structure to the cerium precursor is 1:1, calculated as cerium element in the cerium precursor and calculated as zirconium element in the core structure.
[0028] It should be understood by those skilled in the art that stirring may be performed to promote uniform mixing, and the stirring time may be adjusted by those skilled in the art according to actual conditions. As an example, the stirring time is 30 minutes.
[0029] Furthermore, in step S2, after the core structure is dissolved and dispersed, the mass concentration of the core structure is 2.9338 g / 50 mL.
[0030] It should be understood by those skilled in the art that in order to promote the dissolution and dispersion of the core structure, a stirring process may be performed. As an example, the stirring time is 30 minutes. In the present invention, the core structure is dispersed in deionized water.
[0031] Furthermore, in step S2, the concentration of aqueous ammonia is 0.9 mol / L-1.1 mol / L.
[0032] Furthermore, in step S2, ammonia water is added dropwise to adjust the pH to 8-10.
[0033] Furthermore, in step S2, the specific method of washing includes washing with distilled water and anhydrous ethanol in sequence until the pH of the product is 7, and the washing is completed.
[0034] Furthermore, in step S2, the drying temperature is 70°C-90°C, and the drying time is 11h-13h.
[0035] Furthermore, in step S2, the calcination temperature is 440°C-460°C, and the calcination time is 3.5h-4.5h.
[0036] Furthermore, in the step S2, the heating rate to reach the calcination temperature is 5.5°C / min-6.5°C / min.
[0037] The invention also provides application of the vanadate catalyst in denitration.
[0038] Furthermore, the denitrification temperature is 180°C-380°C.
[0039] Furthermore, the denitrification temperature is 180°C-230°C.
[0040] The embodiments of the present invention have the following technical effects: 1. The vanadate catalyst of the present invention has a core-shell structure, wherein the cerium in the shell structure has excellent oxygen storage capacity and release capacity, and can regulate the supply of oxygen through the oxygen storage and release paths during the reaction, thereby promoting the valence change of the vanadium and zirconium elements in the core structure, thereby improving the redox ability of the catalyst, thereby improving the catalytic activity of the vanadate catalyst at low temperatures; and the core structure vanadium and zirconium are evenly dispersed in the catalyst and exist in an amorphous form, which is conducive to the uniform distribution of active sites in the catalyst, thereby facilitating the full redox reaction between the core structure and the shell structure, thereby more conducive to improving the catalytic activity of the vanadate catalyst at low temperatures. In addition, the cerium dioxide in the shell structure of the present invention has a strong covalent bond with sulfur dioxide, which promotes sulfur dioxide to be preferentially adsorbed on cerium dioxide and oxidized and solidified by lattice oxygen, thereby protecting the core structure from sulfur dioxide poisoning. It can be seen that the core structure of the present invention further improves the sulfur resistance of the vanadate catalyst.
[0041] 2. The vanadate catalyst obtained by the present invention maintains a NO conversion rate of 90% in the sulfur resistance stability test.
[0042] 3. This product has excellent low-temperature SCR catalytic performance, with a NO conversion rate of more than 80% within 180℃-400℃, and is suitable for a variety of low-temperature catalytic scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 It is a SEM image and EDS scanning image provided by the embodiment of the present invention, wherein, Figure 1 a is the SEM image of Example 1, Figure 1 b is the SEM image of Example 3, Figure 1 c is the electronic image of Example 1, Figure 1 d in the figure is the EDS scan of Example 1, Figure 1 e is the Zr element distribution diagram in Example 1, Figure 1 f is the Ce element distribution diagram in Example 1, Figure 1 g is the V element distribution diagram in Example 1, Figure 1 h is the O element distribution diagram in Example 1.
[0045] Figure 2 is the XRD diagram of the embodiment of the present invention.
[0046] Figure 3 It is the NH3-TPD diagram of the embodiment of the present invention.
[0047] Figure 4 is an H2-TPR diagram of an embodiment of the present invention.
[0048] Figure 5 It is a graph showing the catalytic activity test results of the embodiments and comparative examples.
[0049] Figure 6 Graph showing nitrogen selection for Examples and Comparative Examples.
[0050] Figure 7 It is a graph of the anti-sulfur test of the embodiment.
[0051] Figure 8 It is a diagram of the anti-sulfur nitrogen selection of the embodiment.
[0052] Fig. 9 is the TEM scanning result of Example 1, wherein, Fig. 9 Figure a is an electron microscope image of Example 1. Fig. 9 b is the distribution diagram of Ce element. Fig. 9 In the figure, c is the distribution diagram of O element. Fig. 9 In the figure d, it is the distribution diagram of V element. Fig. 9 e is the Zr element distribution diagram, Fig. 9 Figure f is the distribution diagram of Ce and Zr elements. DETAILED DESCRIPTION
[0053] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0054] In a first aspect, some embodiments of the present invention provide a vanadate catalyst having a core-shell structure, wherein the core structure is zirconium vanadate and the shell structure is cerium dioxide.
[0055] The vanadate catalyst in the present invention has a core-shell structure, wherein the cerium in the shell structure has excellent oxygen storage and release capabilities, and can regulate the supply of oxygen through oxygen storage and release pathways during the reaction, thereby causing the vanadium and zirconium elements in the core structure to change valence, thereby improving the redox ability of the catalyst, and thereby improving the catalytic activity of the vanadate catalyst at low temperatures.
[0056] In some embodiments, the vanadium and zirconium of the zirconium vanadate are in an amorphous state and are uniformly dispersed in the core structure.
[0057] The vanadium and zirconium in the core structure are evenly dispersed and can fully cooperate with the cerium in the shell structure, thereby further enhancing the catalytic activity of the catalyst at low temperatures.
[0058] In a second aspect, some embodiments of the present invention also provide a method for preparing the vanadate catalyst, the preparation method comprising: Step S1: adding a solution containing ammonium metavanadate to a solution containing a zirconium precursor, mixing evenly, adding ammonia water to adjust the pH, performing a hydrothermal reaction, performing solid-liquid separation, washing, drying, and calcining to obtain a core structure; Step S2: dissolving and dispersing the core structure, adding a cerium precursor, mixing evenly, dropping ammonia water to adjust the pH, solid-liquid separation, washing, drying, and calcining to obtain a vanadate catalyst with a core-shell structure.
[0059] In the method of the present invention, a core structure in which vanadium and zirconium are distributed in an amorphous form is first prepared, and then a cerium dioxide coating layer is deposited on the surface of the core structure. In the preparation of the shell structure, the concentration and dripping speed of ammonia water are controlled to enable cerium dioxide to be evenly dispersed on the surface of the core structure.
[0060] In some embodiments, the zirconium precursor includes one or more of zirconium nitrate, zirconium oxynitrate, and zirconium nitrate pentahydrate.
[0061] In some embodiments, in the solution containing ammonium metavanadate, the concentration of the ammonium metavanadate in the solution is 0.24 mol / L in terms of vanadium ions.
[0062] In some embodiments, in the solution containing the zirconium precursor, the concentration of the zirconium precursor in the solution is 0.24 mol / L in terms of zirconium ions.
[0063] In some embodiments, in step S1, after uniform mixing, the ammonium metavanadate is calculated as vanadium element, the zirconium precursor is calculated as zirconium element, and the molar concentration ratio of the ammonium metavanadate and the zirconium precursor is 1:1.
[0064] In some embodiments, the method for preparing the solution containing ammonium metavanadate comprises dissolving and dispersing the ammonium metavanadate in deionized water.
[0065] In some embodiments, the method for preparing the solution containing the zirconium precursor comprises dissolving and dispersing the zirconium precursor in deionized water.
[0066] In some embodiments, the uniformly mixed solution may be stirred before the hydrothermal reaction to enable the solute to be evenly dispersed, and the stirring time is 50 min-70 min.
[0067] In some embodiments, in step S1, the concentration of aqueous ammonia is 0.9 mol / L-1.1 mol / L.
[0068] In some embodiments, in step S1, ammonia water is added dropwise to adjust the pH to 9.
[0069] In some embodiments, in step S1, the temperature of the hydrothermal reaction is 170° C.-190° C., and the time of the hydrothermal reaction is 11 h-13 h.
[0070] In some embodiments, in step S1, the specific method of washing includes washing with distilled water and anhydrous ethanol in sequence until the pH of the product is 7, and the washing is completed.
[0071] In some embodiments, in step S1, the drying temperature is 70° C.-90° C., and the drying time is 11 h-13 h.
[0072] In some embodiments, in step S1, the calcination temperature is 440° C.-460° C., and the calcination time is 3.5 h-4.5 h.
[0073] In some embodiments, in step S1, the heating rate to reach the calcination temperature is 5.5°C / min-6.5°C / min.
[0074] In some embodiments, the cerium precursor includes one or more of cerium nitrate and cerium nitrate hexahydrate.
[0075] In some embodiments, in step S2, after uniform mixing, the molar concentration ratio of the core structure to the cerium precursor is 1-2:1-4, calculated as cerium element in the cerium precursor and zirconium element in the core structure.
[0076] In the present invention, the coating amount of cerium dioxide on the surface of the core structure can be adjusted by controlling the molar concentration ratio of the core structure to the cerium precursor. When more cerium dioxide is generated, the pore structure of the core structure will be blocked. When less cerium dioxide is generated, more oxygen cannot be provided, and the valence of vanadium and zirconium is less, the redox ability of the catalyst is reduced, and the catalytic activity is affected. Therefore, in the present invention, the molar concentration ratio of the core structure to the cerium precursor is controlled to be 1-2:1-4.
[0077] In some embodiments, in step S2, after uniform mixing, the molar concentration of the cerium precursor is calculated as cerium element, and the molar concentration of the core structure is calculated as zirconium element, and the molar concentration of the core structure and the cerium precursor is in a ratio of 1:1.
[0078] In some embodiments, in step S2, after the core structure is dissolved and dispersed, the mass concentration of the core structure is 2.9338 g / 50 mL.
[0079] In some embodiments, in step S2, the concentration of aqueous ammonia is 0.9 mol / L-1.1 mol / L.
[0080] In some embodiments, in step S2, ammonia water is added dropwise to adjust the pH to 8-10.
[0081] In some embodiments, in step S2, the specific method of washing includes washing with distilled water and anhydrous ethanol in sequence until the pH of the product is 7, and the washing is completed.
[0082] In some embodiments, in step S2, the drying temperature is 70° C.-90° C., and the drying time is 11 h-13 h.
[0083] In some embodiments, in step S2, the calcination temperature is 440° C.-460° C., and the calcination time is 3.5 h-4.5 h.
[0084] In some embodiments, in step S2, the heating rate to reach the calcination temperature is 5.5°C / min-6.5°C / min.
[0085] In a third aspect, some embodiments of the present invention also provide the use of the vanadate catalyst in denitration at a temperature of 180°C-380°C.
[0086] In a fourth aspect, some embodiments of the present invention also provide the use of the vanadate catalyst in denitration.
[0087] In some embodiments, the denitration temperature is 180°C-380°C.
[0088] In some embodiments, the denitration temperature is 180°C-230°C.
[0089] The following is described in conjunction with some specific embodiments and comparative examples: Embodiment 1: (1) Dissolve 2.5759 g of vanadium nitrate pentahydrate in 25 mL of deionized water and stir for 30 min to obtain solution A.
[0090] (2) At the same time, 0.70164 g of ammonium metavanadate was dissolved in 25 mL of deionized water, heated to 80 °C in a water bath, and stirred for 30 min to obtain solution B, in which the molar ratio of Zr ions to V ions was 1:1.
[0091] (3) Stir solution A and solution B separately until they are completely dissolved, then slowly pour solution B into solution A and continue stirring for 1 hour to obtain solution C.
[0092] (4) Prepare 1 mol / L ammonia solution, titrate solution C to pH = 9, and stir for 1 h.
[0093] (5) The resulting mixture was placed in a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 180 °C for 12 h.
[0094] (6) After the reactor was cooled to 25°C, the slurry was filtered and washed with distilled water and ethanol several times until the pH value was 7.
[0095] (7) The obtained filter cake was then placed in an oven and dried at 80°C for 12 h. The dried sample was placed in a muffle furnace and calcined at 450°C for 4 h at a rate of 6°C / min to obtain a core structure; (8) Grind 2.9338 g of the core structure into powder and disperse it in 50 mL of deionized water and stir for 30 min.
[0096] (9) 2.6053 g of cerium nitrate hexahydrate was added and dissolved in the solution obtained in step (8), and the mixture was stirred continuously to form a mixed solution at room temperature, wherein the molar ratio of Zr ions to Ce ions was 2:1.
[0097] (10) Add 1 mol / L ammonia solution dropwise to the mixed solution until the pH value of the mixed solution reaches 8-10.
[0098] (11) Solid-liquid separation: the separated solution is washed with distilled water and ethanol several times until the pH value is 7.
[0099] (12) The obtained filter cake was then placed in an oven and dried at 80 °C for 12 h. The dried sample was placed in a muffle furnace and calcined at 450 °C for 4 h at a rate of 6 °C / min.
[0100] Embodiment 2: Step (1) to step (7) are the same as in Example 1 (8) Grind 2.9338 g of the core structure into powder and disperse it in 50 mL of deionized water and stir for 30 min.
[0101] (9) 5.2106 g of cerium nitrate hexahydrate was added and dissolved in the solution obtained in step (8), and the mixture was stirred continuously to form a mixed solution at room temperature, wherein the molar ratio of Zr ions to Ce ions was 1:1.
[0102] (10) Add 1 mol / L ammonia solution dropwise to the mixed solution until the pH value of the mixed solution reaches 8-10.
[0103] (11) Solid-liquid separation: the separated solution is washed with distilled water and ethanol several times until the pH value is 7.
[0104] (12) The obtained filter cake was then placed in an oven and dried at 80 °C for 12 h. The dried sample was placed in a muffle furnace and calcined at 450 °C for 4 h at a rate of 6 °C / min.
[0105] Embodiment 3: Step (1) to step (7) are the same as in Example 1 (9) Grind 2.9338 g of the core structure into powder and disperse it in 50 mL of deionized water and stir for 30 min.
[0106] (9) 20.8426 g of cerium nitrate hexahydrate was added and dissolved in the solution obtained in step (8), and the mixture was stirred continuously to form a mixed solution at room temperature, wherein the molar ratio of Zr ions to Ce ions was 1:4.
[0107] (10) Add 1 mol / L ammonia solution dropwise to the mixed solution until the pH value of the mixed solution reaches 8-10.
[0108] (11) Solid-liquid separation: the separated solution is washed with distilled water and ethanol several times until the pH value is 7.
[0109] (12) The obtained filter cake was then placed in an oven and dried at 80 °C for 12 h. The dried sample was placed in a muffle furnace and calcined at 450 °C for 4 h at a rate of 6 °C / min.
[0110] Comparative Example 1: (1) Dissolve 2.5759 g of vanadium nitrate pentahydrate in 25 mL of deionized water and stir for 30 min to obtain solution A.
[0111] (2) At the same time, 0.70164 g of ammonium metavanadate was dissolved in 25 mL of deionized water, heated to 80 °C in a water bath, and stirred for 30 min to obtain solution B, in which the molar ratio of Zr ions to V ions was 1:1.
[0112] (3) Stir solution A and solution B separately until they are completely dissolved, then slowly pour solution B into solution A and continue stirring for 1 hour to obtain solution C.
[0113] (4) Prepare 1 mol / L ammonia solution, titrate solution C to pH = 9, and stir for 1 h.
[0114] (5) The resulting mixture was placed in a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 180 °C for 12 h.
[0115] (6) After the reactor was cooled to 25°C, the slurry was filtered and washed with distilled water and ethanol several times until the pH value was 7.
[0116] (7) The obtained filter cake was then placed in an oven and dried at 80°C for 12 h. The dried sample was placed in a muffle furnace and calcined at 450°C for 4 h at a rate of 6°C / min to obtain a catalyst.
[0117] The present invention also obtains embodiment and comparative example and tests: BET test: Kubo X1000 BET specific surface area analyzer was used.
[0118] SEM test: Gemini SEM 360 was used for electron microscope scanning.
[0119] XRD test: A Bruker D8 Advance X-ray diffractometer was used.
[0120] NH3-TPD test: using BelCata II instrument.
[0121] H2-TPR test: using BelMass instrument.
[0122] Catalyst denitrification activity test: The catalysts prepared in the examples and comparative examples were tested in a fixed bed reactor. The reaction mixers were NO (500 ppm), NH3 (500 ppm), O2 (10%), and N2 was used as the balance gas. The reaction space velocity was 50000 h -1 The test temperature range is 130℃-430℃, and the dwell time is 60min every 50℃.
[0123] The calculation formula of NO removal rate is as follows:
[0124] The calculation formula of N2 selectivity is as follows:
[0125] Results and Analysis: Table 1 BET characterization results of examples
[0126] A catalyst with a core-shell structure is successfully obtained through the method of the present invention. The core structure of the catalyst is zirconium vanadate, and the vanadium and zirconium elements in the core structure are uniformly dispersed, presenting an amorphous structure; the shell structure of the catalyst is cerium dioxide, and the cerium in the shell structure not only has excellent oxygen storage and release capabilities, but can also regulate the supply of oxygen through oxygen storage and release pathways during the reaction, thereby causing the vanadium and zirconium elements in the core structure to change valence, thereby improving the redox ability of the catalyst; and the cerium dioxide in the shell structure has a strong covalent bond with sulfur dioxide, causing sulfur dioxide to be preferentially adsorbed on the cerium dioxide and oxidized and solidified by lattice oxygen, thereby protecting the core structure from sulfur dioxide poisoning. In addition, the vanadium and zirconium in the core structure are uniformly dispersed, which is conducive to the full redox reaction between the core structure and the shell structure, and is further conducive to improving the catalytic activity of the vanadate catalyst at low temperatures. It can be used in Figure 1-Figure 2 and Fig. 9 Verification in.
[0127] in Figure 1 (a) and Figure 1 (b) are SEM images of the catalysts obtained in Example 1 and Example 3, respectively. It can be seen that the surface of the catalyst of the present invention presents irregular spherical protrusions, which is beneficial to increase the specific surface area of the material, thereby promoting the adsorption and mass transfer of reactants, and as the loading amount of CeO2 increases, the accumulation of CeO2 cubic crystals can be clearly observed. Figure 1 (c)- Figure 1 (h) is the EDS spectrum scanning result of Example 1, which is used to characterize the distribution of each element of the catalyst. It can be observed that the distribution of the three elements Zr, V and O on the surface of the catalyst of Example 1 is relatively uniform, which is conducive to exposing more active sites and promoting the SCR reaction.
[0128] Figure 2 The XRD diagrams of the catalysts obtained in Examples 1 to 3 show that the CeO2 crystal form is obvious in Examples 1 to 3. And as the CeO2 loading increases, the CeO2 peak intensity increases, and no obvious ZrVO4 crystal form is found in the XRD diagram. Combined with the SEM image, it is speculated that this is due to the uniform dispersion of vanadium and zirconium elements.
[0129] exist Fig. 9 In the embodiment, the coating structure of Example 1 was detected by TEM scanning electron microscope. Fig. 9 (a) It can be seen that fine particles are accumulated at the edge of the catalyst. Fig. 9 Figure (f) shows that the red shadow area belonging to the Ce element is significantly larger than the green area represented by the Zr element, indicating that the small particles accumulated in the outer layer belong to CeO2. This shows that CeO2 is located in the outer layer of the ZrVO4 catalyst and the catalyst has a core-shell structure.
[0130] In the present invention, taking Example 1 as an example, the sulfur resistance of the catalyst was further studied. Figure 7-Figure 8 As shown, the catalyst obtained by the present invention has excellent sulfur resistance. The NO conversion rate of the catalyst in Example 1 at 230°C when 200ppm SO2 is introduced is about 90%. It also further verifies that the shell structure cerium dioxide of the present invention can be used as a sacrificial site to preferentially combine with SO2, thereby ensuring the activity of the active sites of the core structure. It can be seen that the shell structure in the present invention further improves the sulfur resistance of the catalyst.
[0131] Characterization results by NH3-TPD Figure 3 It can be seen that the desorption peaks of Examples 1 to 3 at 145°C, 125°C and 130°C are attributed to the desorption of NH3 species at weak Br⌀nsted acid sites, and no peaks at this position are observed on CeO2. The peaks of Example 1 catalyst at 200°C and 300°C are attributed to the desorption of NH3 species adsorbed on strong Br⌀nsted acid sites, which are Figure 3 It can be seen that the catalyst has the maximum desorption amount within this range, indicating that the strong Br⌀nsted acid is mainly involved in the adsorption and activation in the reaction and is the main reaction active site.
[0132] According to the H2-TPR characterization results Figure 4 It can be seen that in the temperature range of 400°C to 550°C, Examples 1 to 3 all show reduction peaks, which are mainly due to Ce 4+ 、Zr 4+ Or surface V 5+ It can be seen from the reduction reaction of complex species such as , that the embodiments of the present invention have stronger reducing properties at relatively low temperatures.
[0133] In the present invention, cerium dioxide is coated on the surface of the core structure as a shell structure. When the coated cerium dioxide is more, the oxygen storage and release capacity of the catalyst can be improved, which is conducive to the valence change of vanadium and zirconium elements, thereby improving the oxidation-reduction ability of the catalyst; and as the cerium dioxide increases, the cerium dioxide crystals will block the internal pores of ZrVO4, thereby covering the active sites and reducing the catalytic activity. Therefore, in the present invention, the molar concentration ratio of the core structure to the cerium precursor is 1-2:1-4, calculated as cerium element in the cerium precursor and zirconium element in the core structure.
[0134] On this basis, the ratio between the core structure and the shell structure in the catalyst was further optimized, as shown in Table 1 and Figure 5As shown. In Table 1, it is found from the comparison of Examples 1 to 3 that with the increase of cerium dioxide, the specific surface area, pore volume and pore size of the catalyst first increase and then decrease, and a larger specific surface area and a smaller pore size are conducive to the adsorption and mass transfer of reactant molecules. Therefore, based on the above factors, it is further preferred that the molar concentration ratio of the core structure to the cerium precursor is 1:1, calculated as cerium element and the core structure is calculated as zirconium element.
[0135] exist Figure 5 It can also be verified that Example 2 has better catalytic activity than Example 1 and Example 3. Figure 5 Compared with the catalyst of comparative example 1, the catalysts of examples 1 to 3 show excellent low-temperature catalytic performance, and the NO conversion rate at 180°C is generally higher than 90%. The NO conversion rate of the catalyst of example 1 reaches 91% at 180°C, and the NO conversion rate is higher than 90% in the temperature window of 180°C-400°C. It can be seen that the catalyst obtained by the present invention has excellent catalytic performance, especially significantly better than the prior art at temperatures below 230°C.
[0136] exist Figure 6 The catalyst of the present invention exhibits excellent N2 selectivity, with N2 selectivity greater than 90% within the overall temperature window.
[0137] It should be noted that the terms used in the present invention are only for describing specific embodiments, rather than limiting the scope of the present application. As shown in the present specification, unless the context clearly indicates an exception, the words "one", "a", "a kind of" and / or "the" do not specifically refer to the singular, but may also include the plural. The terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method or device. In the absence of more restrictions, the elements defined by the sentence "include one..." do not exclude the presence of other identical elements in the process, method or device including the elements.
[0138] It should also be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. Unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", etc. should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0139] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.
Claims
1. A vanadate catalyst, characterized in that The vanadate catalyst has a core-shell structure, wherein the core structure is zirconium vanadate and the shell structure is cerium dioxide.
2. The vanadate catalyst according to claim 1, characterized in that The vanadium and zirconium of the zirconium vanadate are in an amorphous state and are uniformly dispersed in the core structure.
3. The method for preparing the vanadate catalyst according to any one of claims 1 to 2, characterized in that: The preparation method comprises: Step S1: adding a solution containing ammonium metavanadate to a solution containing a zirconium precursor, mixing evenly, adding ammonia water to adjust the pH, performing a hydrothermal reaction, performing solid-liquid separation, washing, drying, and calcining to obtain a core structure; Step S2: dissolving and dispersing the core structure, adding a cerium precursor, mixing evenly, dropping ammonia water to adjust the pH, solid-liquid separation, washing, drying, and calcining to obtain a vanadate catalyst with a core-shell structure.
4. The preparation method according to claim 3, characterized in that: The zirconium precursor includes one or more of zirconium nitrate, zirconium oxynitrate, and zirconium nitrate pentahydrate; The cerium precursor includes one or more of cerium nitrate and cerium nitrate hexahydrate.
5. The preparation method according to claim 3, characterized in that: In the solution containing ammonium metavanadate, the concentration of the ammonium metavanadate in the solution is 0.24 mol / L in terms of vanadium ions; In the solution containing the zirconium precursor, the concentration of the zirconium precursor in the solution is 0.24 mol / L in terms of zirconium ions; In the step S1, after uniform mixing, the ammonium metavanadate is calculated as vanadium element, the zirconium precursor is calculated as zirconium element, and the molar concentration ratio of the ammonium metavanadate and the zirconium precursor is 1:
1.
6. The preparation method according to claim 3, characterized in that: In step S1, the concentration of ammonia water is 0.9 mol / L-1.1 mol / L; In the step S1, ammonia water is added dropwise to adjust the pH to 9; In step S1, the temperature of the hydrothermal reaction is 170°C-190°C, and the time of the hydrothermal reaction is 11h-13h; In step S1, the drying temperature is 70°C-90°C, and the drying time is 11h-13h; In step S1, the calcination temperature is 440°C-460°C, and the calcination time is 3.5h-4.5h; In the step S1, the heating rate to reach the calcination temperature is 5.5°C / min-6.5°C / min.
7. The preparation method according to claim 3, characterized in that: In the step S2, after uniform mixing, the molar concentration ratio of the cerium precursor in terms of cerium element and the core structure in terms of zirconium element is 1-2:1-4; In the step S2, after the core structure is dissolved and dispersed, the mass concentration of the core structure is 2.9338 g / 50 mL.
8. The preparation method according to claim 3, characterized in that: In step S2, the concentration of ammonia water is 0.9 mol / L-1.1 mol / L; ammonia water is added dropwise to adjust the pH to 8-10.
9. The preparation method according to claim 3, characterized in that: In step S2, the drying temperature is 70°C-90°C, and the drying time is 11h-13h; In step S2, the calcination temperature is 440°C-460°C, and the calcination time is 3.5h-4.5h; In the step S2, the heating rate to reach the calcination temperature is 5.5°C / min-6.5°C / min.
10. Use of the vanadate catalyst according to any one of claims 1 to 2 or the vanadate catalyst obtained by the preparation method according to any one of claims 3 to 9 in denitration.
Citation Information
Patent Citations
SCR (selective catalyctic reduction) low-temperature denitrification catalyst with nano core-shell structure and preparation method thereof
CN102335604A
Zirconium doped cerium vanadate denitration catalyst, preparation method and application
CN105032395A
CeO2@MnOx low-temperature SCR flue gas denitrification catalyst as well as preparation method thereof and application thereof
CN106732536A
Zirconium vanadate catalyst as well as preparation method and application thereof
CN118162127A
Micron-scale cerium oxide particle having multi-core single-shell structure and preparation method therefor
US20180029012A1
Cited By
Rare-earth-based hydrogenation catalyst and preparation method thereof
CN120421038A
